Knowledge and Attitude Regarding Non-Pharmacological Pain Relief Methods during Labor among Midwives and Nurses at Madina - Al-harbi, Manal Mejzi; Khamis, Hamdia M. (British Journal of Healthcare and Medical Research, 2022)
Background: Pain during labour is a complicated, multidimensional, and subjective issue that both the expecting mother and the maternity healthcare provider are concerned about. The aim was to assess knowledge and attitudes regarding non-pharmacological pain relief methods during labour among midwives and nurses at Madina. Subjects and Methods: The study employed a quantitative descriptive cross-sectional study design; 158 participants (midwives and nurses) were conveniently selected. The study was carried out in the Labour ward and Antenatal ward at Maternity at Medina and the Child Hospital at Medina hospital from January to February (2022). Data was collected through a self-administered questionnaire. Results: The study revealed that 51.9% of participants had adequate knowledge, while 48.1% had inadequate knowledge. In addition, 60.8% of them have a good attitude. Factors associated significantly with knowledge regarding non-pharmacological pain relief include education, working area, and the profession. In addition, the present study reflects that there is a positive correlation between participants' knowledge of non-pharmacological pain relief and their attitude. Recommendations: Nurses and midwives should be involved in several educational and training courses and attend different workshops, conferences, and seminars on non-pharmacological pain relief during labour. Nurses and midwives should utilize the methods of non-pharmacological pain relief during labour to alleviate the complications of pharmacological pain relief as much as possible. Further studies should be conducted by other researchers to investigate other factors that affect and enhance the level of non-pharmacological pain relief methods. Researchers can also incorporate the domain of practise within their future studies.